2013
DOI: 10.1186/1471-2164-14-196
|View full text |Cite
|
Sign up to set email alerts
|

Structured association analysis leads to insight into Saccharomyces cerevisiaegene regulation by finding multiple contributing eQTL hotspots associated with functional gene modules

Abstract: BackgroundAssociation analysis using genome-wide expression quantitative trait locus (eQTL) data investigates the effect that genetic variation has on cellular pathways and leads to the discovery of candidate regulators. Traditional analysis of eQTL data via pairwise statistical significance tests or linear regression does not leverage the availability of the structural information of the transcriptome, such as presence of gene networks that reveal correlation and potentially regulatory relationships among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The eQTL analysis is a strategy for discovering the complex patterns correlating genotypic data of genetic variants to global microarray gene expression data from a population of individuals (Curtis et al 2013). By searching the University of Michigan Center for Statistical Genetics eQTL database (http://www.sph.umich.edu/csg/liang/imputation/), we found that the common risk allele G of SNP rs1122608 was negatively associated with the expression level of the SFRS3 gene (Affymetrix HG U133 Plus 2.0 probe:232392_at, effect = −0.344, P = 0.00041) (Dixon et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The eQTL analysis is a strategy for discovering the complex patterns correlating genotypic data of genetic variants to global microarray gene expression data from a population of individuals (Curtis et al 2013). By searching the University of Michigan Center for Statistical Genetics eQTL database (http://www.sph.umich.edu/csg/liang/imputation/), we found that the common risk allele G of SNP rs1122608 was negatively associated with the expression level of the SFRS3 gene (Affymetrix HG U133 Plus 2.0 probe:232392_at, effect = −0.344, P = 0.00041) (Dixon et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 692 SNPs was determined based on the GAMMAR p-value< 5 × 10 −5 (Figure 2). We next divided the whole yeast genome into 603 20-kb bins, and then SNPs with the smallest GAMMAR p-values were selected in each bin for comparison with the previous yeast eQTL studies [21,22]. We determined that 117 trans-eQTLs had 59 eGenes on three chromosomes.…”
Section: Gammar Analysis Using the Yeast Datasetmentioning
confidence: 99%
“…Collectively, we defined the six bins as trans-regulatory hotspots and 59 eGenes as putative regulators. Of the 59 total eGenes, nine had been previously identified [21,22,24] (Table 1). In four previous studies, MATing type protein ALPHA 1; III:190000 (MATALPHA1) was reported to be a casual regulator [21,[25][26][27], and Killer toxin REsistant 33; XIV:360000 (KRE33) was recently identified as a putative causal regulator [24].…”
Section: Gammar Analysis Using the Yeast Datasetmentioning
confidence: 99%
“…In chromosome V, around the locus of URA3 we find a cisacting eQTL that has a trans-acting effect on URA1 (chromosome XI) and URA4 (chromosome XII), the three of them taking part in the biosynthesis of pyrimidines (Yvert et al 2003;Curtis et al 2013). As can be easily seen from Figure 6, and consistent with previous observations (Yvert et al 2003), few of the eQTLs directly affect transcription factors, such as the ARR1 gene in chromosome XI, or RNA-binding proteins, such as NOP8 in chromosome V.…”
Section: Performance Comparison Against Another Methodsmentioning
confidence: 99%
“…This eQTL is cisassociated with the gene MATALPHA1, which is expressed in haploids of the alpha-mating type and has been previously reported as a candidate regulator of the rest of genes associated with this locus (Yvert et al 2003;Curtis et al 2013). This locus is trans-associated with two other genes in the same chromosome (HMLALPHA1, HMRA1) and to a set of genes distributed throughout the genome [STE2, STE3, STE6, AFB1, BAR1, MF(ALPHA)1, MFA2], which are all involved in the regulation of mating-type-specific transcription.…”
Section: Performance Comparison Against Another Methodsmentioning
confidence: 99%